The Role of the Clean Development Mechanism in Achieving China’s Goal of a Resource Efficient and Environmentally Friendly Society - Jia, Ruiyue; Guo, Xiumei; Marinova, Dora (Springer Science+Business Media B.V. (Kluwer Academic Publishers), 2013)
This paper examines the impact of the clean development mechanism (CDM) on China’s progress in building a resource-efficient and environmentally friendly society, referred to as a dual-goal society. It presents China’s CDM activities from the perspective of policy directions, administrative arrangements and capacity building as well as outlines the regional trends and distribution of CDM projects across China’s 30 provinces. Based on regression analysis of 2006–2009 panel data, the research was able to provide estimates at provincial level of the impacts of CDM activities on China’s CO2 emission intensity, SO2 emission intensity and industrial dust emission intensity. The study concludes that the active CDM projects are mainly located in the less-developed central and west China where they have provided increased opportunities for sustainable development. Furthermore, the successful implementation of CDM projects across the country has significantly decreased the emission intensity of CO2, SO2 and industrial dust, which means that these activities have enhanced China’s ability to build the desired dual-goal society.